Neuropsychiatric Symptoms in Dementia: Considerations for Pharmacotherapy in the USA - Stephanie V. Phan; Sharmon Osae; John C. Morgan; Mfon Inyang; Susan C. Fagan (Adis, Springer Healthcare, 2019)
Abstract Dementia affects all domains of cognition. The relentless progression of the disease after diagnosis is associated with a 98% incidence of neuropsychiatric symptoms (NPS) at some point in the disease, including depression, psychosis, agitation, aggression, apathy, sleep disturbances, and disinhibition. These symptoms can be severe and lead to excess morbidity and mortality. The purpose of this article was to describe current literature on the medication management of NPS of dementia and highlight approaches to and concerns about the pharmacological treatment of NPS in the USA. Guidelines and expert opinion favor nonpharmacologic management of NPS as first-line management. Unfortunately, lack of adequate caregiver training and a high failure rate eventually result in the use of psychotropic agents in patients with dementia. Various psychotropic medications have been studied, although how they should be used in the management of NPS remains unclear. A systematic approach to evaluation, treatment, and monitoring, along with careful documentation and evidenced-based agent and dose selection, is likely to reduce risk and improve patient outcomes. Considerations should be given to the NPS presentation, including type, frequency, and severity, when weighing the risks and benefits of initiating, continuing, or discontinuing psychotropic management. Use of antidepressants, sedative/hypnotics, antipsychotics, and antiepileptic agents should include a clear and documented analysis of risk and benefit in a given patient with dementia.